Histórias de violência sexual compartilhadas em rede: uma análise da mobilização #primeiroassédio - Marques, Ana Cesaltina Barbosa (2022)
Based on traditions of narrative research in Social Psychology, this case study examines a campaign that led thousands of Brazilian victims of sexual violence to share their testimonies tagged with the hashtag #Firstharassment on the social networking site Twitter. It was the NGO Think Olga that called for this action in October 2015. The present research investigates how this mobilization led people to overcome obstacles erected by a patriarchal culture and publicly share memories and marks left by aggression. There is a thesis arising in this context which states that the network conversation between the narrators made it possible to negotiate new parameters to define sexual violence and offer resources to speak about it. A mediated narrative analysis is the thread that takes the discussion through concepts and debates based on feminist epistemologies. The study is guided by the social constructionist paradigm, which considers phenomena related to subjectivity and sociability as historical and cultural constructions forged in everyday interactions. This perspective with its critical emphasis favors the observation of power relations engendered by gender issues. The analyzed corpus consists of 15 thousand tweets, retweets, replies and mentions, considered units of analysis, which are presented as small stories (BAMBERG; GEORGAKOPOULOU, 2008). A subset of 4 thousand unique tweets was analyzed using Antconc corpus linguistics software and supported by Excel. Thanks to the technical and semantic connection produced by the hashtag #First harassment it is possible to approach the compilation of individual stories as one shared story (PAGE, 2018) that is shaped as a network narrative (PAGE; HARPER; FROBENIUS, 2013). The methodology applied when examining the corpus is inspired by a model of mediated narrative analysis formulated by Page (2018): It proposes an approach at the three levels text, context and social meanings. In order to navigate the corpus, which was anonymized to preserve the privacy of the narrators, most frequent narrative patterns are sought as well as aspects that are presented in a veiled way, since they evidence how culture resists to confront them. This makes it possible to know the characters that are most cited in the memories of violence; environments and circumstances that are most susceptible to occurrences; in addition to narrative resources that are used to name situations the narrator went through. The investigation identifies influences of dominant narratives in the formulation of small stories which express forces that act daily so as to objectify women. Sexual violence presents itself as a device to shape gender performance in the Brazilian culture. In the shared narrative, the gender variable is protagonist and constitutes the collective voice while other issues, such as race and class, are secondary and move into the background. It may be suggested that the campaign projection is a result of theauthority produced by the collective narrator pole that, although not in unison, anointed itself with legitimacy to dispute the turns of speech and performatically denounce how permissive the Brazilian culture is to practices of sexual abuse of girls and women.